Doctoral Education through the Lenses of the Bologna Process - Baptista, Ana (International Journal of Humanities and Social Science Research, 2016)
The agenda of Higher Educational institutions and other organisations reveals a growing concern with the extension and impact of research at the postgraduate level. Doctoral studies are thus acquiring a greater significance and value. The international and European context demonstrates the existence of an increasing number and a greater diversity of research students enrolling in postgraduate studies, particularly in doctoral programmes. Consequently, it is the purpose of this paper to examine doctoral education through the lenses of the Bologna Process. This perspective is chosen particularly due to the importance of Bologna at educational, political, economic, and social levels in Europe but also beyond. In fact, among other discourses, Bologna has been shaping the ‘trends’ relating to doctoral education. Alongside with Bologna Ministerial documents, others from some consultative members (the so-called ‘E4 group’) are analysed. In the last section, some main challenges to doctoral education are highlighted.